Mastitis Incidence in First-Calf Heifers on the Small Farms of the Republic of Armenia - Melkonyan, Zh. S.; Khotsanyan, V. V.; Sukiasyan, K. A.; Nikoghosyan, E. A. (ՀԱԱՀ հիմնադրամ)
The article presents the results of scientific research aimed at studying mastitis incidence in first-calf heifers and the affection of udder quarters in the mastitic first-calf heifers on eleven small farms in the Kotayk and Ararat regions of Armenia. According to the results of scientific research, subclinical mastitis incidence in first-calf heifers made 32.3 %, while the number of affected udder quarters was 78 (per 100 animal units). The clinical mastitis was diagnosed in 10.7 % of firstcalf heifers and the number of affected udder quarters was 25. Upon the research results, the experimental farms were provided with practical recommendations on prevention of mastitis in first-calf heifers.
Keywords: Veterinary Science and Animal Breeding